Ten years ago, what was the main etiology of intestinal obstructions? Historical perspective: A retrospective cohort study. - Çalışkan, Yahya Kemal (Journal of Surgery and Medicine, 2017)
Aims: Etiology of intestinal obstruction differs between countries. This study was designed to review a large series of patients with intestinal obstruction in an attempt to represent our historical aspect of experience in Turkey 10 years ago. Methods: A review of the charts of 1387 patients admitted for intestinal obstruction during an 8-year period (2000 through 2007) was carried out. Results: Cases were divided into two groups. Group A consisted of 1186 (85.5%) patients underwent operation. The remaining 201 (14.5%) patients managed non-operatively constituted group B. External strangulated hernias (inguinal, femoral, umbilical and incisional) were the most common cause of intestinal obstruction in group A, accounting for 46% of cases. Neoplasms and adhesions were common cause accounting for 19% and 18% of cases respectively. Conclusion: External hernias are the most common cause of intestinal obstruction in our hospital. Increased efforts to repair external hernias electively before strangulation occurs are likely to reduce the incidence. Some major changes in etiology rank are present in current literature. New studies have to be performed to reveal current condition.